PREVALENCE AND GENDER CHARACTERISTICS OF OBESITY IN ADOLESCENTS IN THE CITY OF PERM - R. M. Ahmedova; L. V. Sofronova; R. N. Trefilov ("Paediatrician" Publishers LLC, 2014)
Background: Currently, there is a well-publicised worldwide increase in obese patients. The origins of adult obesity, in the majority of cases, are in children. Objective: Our aim was to study the prevalence and gender features of excess weight and obesity in adolescents in Perm. Methods: The study included adolescents aged 13-14, living in the city of Perm. Medical examinations were compared in statistics from 2005 and 2013. Weight, height and waist circumference were measured on all children. Body mass index was calculated, as was a standard deviation coefficient. Sexual development was evaluated according to the criteria of Tanner. Results: 828 adolescents were viewed (444 in 2005 and 384 in 2013). The prevalence of overweight adolescents in 2005 was 12.5%, including 3.1% who were obese. In 2013, 20.3% of adolescents were diagnosed as overweight, with 5.5% being diagnosed as obese. Abdominal obesity to type was diagnosed in 52.4% of obese children. Over the past 8 years, the number of adolescents who are overweight and obese has increased by more than half. A statistically significant increase has beenrecorded for overweight adolescents (ᵪ2 = 5,16; p = 0,023). In adolescents with excess body weight, growth rates were higher than in those children with either normal body weight or obesity; these differences were statistically significant in boys (p = 0.016). The total score of puberty in boys who were overweight was statistically significantly higher than adolescents with normal body weight orobesity (p = 0.0116). Conclusion: The percentage of children who are overweight and obese hasincreased by 74% and 67%, respectively over an 8-year period, resulting ina statistically significant increase in relation to overweight children. There was a significant increase in the number of teenage girls who are overweight.